Foliar Application of NH4+/NO3– Ratios Enhance the Lodging Resistance of Soybean Stem by Regulating the Physiological and Biochemical Mechanisms Under Shade Conditions - Raza, Ali; Yin, Chunying; Asghar, Muhammad Ahsan; Ihtisham, Muhammad; Shafiq, Iram; Cheng, Bin; Ghafoor, Abuzar; Javed, Hafiz Hassan; Iqbal, Tauseef; Khan, Nawab; Liu, Weiguo; Yang, Wenyu (Frontiers in Plant Science, 2022)
In maize-soybean intercropping systems (MSIR), the tall stature maize plants reduced light intensity which resulted in shade avoidance responses to soybean thereby causing the lodging stress. NH4+ and NO3- are key inorganic forms of nitrogen which regulate various morpho-physiological and biochemical activities in plants. In order to increase the soybean stem lodging resistance, a two-year field trial was conducted to evaluate the impact of different ratios and concentrations of NH+4/NO-3 on the morpho-physiological and biochemical characteristics of soybean stem under shade conditions. Our findings displayed that, the T2 (25/75) and T3 (50/50) treatments alleviated the shading stress by improving the photosynthetic activity, biomass accumulation, carbohydrates contents and lignin related enzymes (POD, CAD, and 4Cl) which led to the improvement in stem lodging resistance. However, the most appropriate ratio (T2) increased the stem snapping resistance 86.84% over T4 treatment and lodging resistance index enhanced by 44.44% as compared to T0 under light and shade conditions, respectively. The T2 and T3 treatments significantly enhanced the lignin and cellulose under both light conditions. In addition, the activities of lignin related enzymes and soybean yield were observed to be prompted at T2 and T3 treatments under shade stress. The correlation analysis revealed the strong relationship between lodging resistance index and stem diameter, stem strength, lignin content, photosynthesis, and lignin related enzymes (POD, CAD, and 4CL) evidencing the strong contribution of lignin and its related enzymes in the improvement of lodging resistance of soybean stem under shade conditions. Collectively, we concluded that optimum NH4+/NO3- ratios (T2 and T3) can boost up the lodging resistance of soybean stem under shade stress.